Two novel MOFs@COFs hybrid-based photocatalytic platforms coupling with sulfate radical-involved advanced oxidation processes for enhanced degradation of bisphenol A. (March 2020) - Lv, Shi-Wen; Liu, Jing-Min; Li, Chun-Yang; Zhao, Ning; Wang, Zhi-Hao; Wang, Shuo
Abstract: Nowadays, the visible-light-driven photocatalysis via advanced photocatalyst for PS activation have promising applications in wastewater treatment. Herein, for the first time, two novel MOFs@COFs hybrid materials (denoted as MIL-101-NH2 @TpMA and UiO-66-NH2 @TpMA) with nitrogen-rich building blocks were fabricated via a feasible step-by-step assembly method, and then employed as efficient photocatalytic platform coupling with sulfate radical-based advanced oxidation processes for the degradation of BPA under visible light irradiation. Detailed analyses revealed that the hybridization of MOFs and COFs could greatly boost visible light absorption, while the heterojunction formed at the interface could effectively facilitate the separation and transfer of photogenerated electron-hole pairs. More importantly, the developed solar/MOFs@COFs/PS system exhibited the excellent degradation ability toward BPA, and an incredible degradation efficiency of 99% was eventually achieved. Possible mechanism for photocatalytic degradation of BPA was also proposed. Furthermore, the prepared composites with great reusability and stability possessed a broad potential for highly effective degradation of various organic contaminants. In short, this work not only demonstrated the combination of MOFs and COFs with C3 N4 active unit was a feasible strategy for improving photocatalytic activities in the degradation of organic contaminants, but also provided some novel inspirations for constructing high-efficient photocatalysts with heterostructure. Graphical abstract: Image 1 Highlights: Two novel MOFs@COFs hybrid materials with C3 N4 active units were first synthesized. Developed solar/MOFs@COFs/PS system exhibited great degradation ability toward BPA. Possible mechanisms for photocatalytic degradation of BPA was proposed. As-obtained composites possessed excellent reusability and stability. Prepared photocatalyst had a broad potential for degradation of various contaminants.